2005
DOI: 10.1108/13673270510582947
|View full text |Cite
|
Sign up to set email alerts
|

Balancing business process with business practice for organizational advantage

Abstract: Purpose-To provide an argument and a practical approach for achieving a balance between business process optimization and the use of human-centred business practices. Design/methodology/approach-The concepts of business process and business practice are positioned in the academic literature with related concepts like tacit and explicit knowledge, routine work, codification and bounded rationality. Process and practice are compared and contrasted prior to the development of a model for their coexistence and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Lock Lee (2005) presents a methodology that is focused on the design and implementation of software products supporting business processes. This is in line with definition (A) of process management, but with a strong focus on the purpose of identifying opportunities for outsourcing and the use of technology to support business suggested by Lock Lee (2005) and Lindsay et al (2003). There were hardly any methodologies found that support definition (B) of process management as a more holistic manner to manage all aspects of the business and as a valuable perspective to adopt in determining organizational effectiveness.…”
Section: Exploring Process Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Lock Lee (2005) presents a methodology that is focused on the design and implementation of software products supporting business processes. This is in line with definition (A) of process management, but with a strong focus on the purpose of identifying opportunities for outsourcing and the use of technology to support business suggested by Lock Lee (2005) and Lindsay et al (2003). There were hardly any methodologies found that support definition (B) of process management as a more holistic manner to manage all aspects of the business and as a valuable perspective to adopt in determining organizational effectiveness.…”
Section: Exploring Process Managementmentioning
confidence: 99%
“…Lock Lee (2005) presents a methodology that is focused on the design and implementation of software products supporting business processes. This is in line with definition (A) of process management, but with a strong focus on the purpose of identifying opportunities for outsourcing and the use of technology to support business suggested by Lock Lee (2005) and Lindsay et al (2003).…”
Section: Approaches and Tools For Process Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Company's products and services must regularly be upgraded to live up to customers' expectation as well as the ability to stand competitors' offering (McAdams & McCormack, 2001).  Opportunity Identification: Ability to organisations to spot out opportunities in the business environment such as deposit money banks are one of the main reasons companies embark on changing or introducing new processes in the organisation (Lindsay, Downs & Lunn, 2003;Lock Lee, 2005).  Improve collective learning: This implies that some organisations adopt new processes for the sole aim of enhancing the knowledge of the employees.…”
Section: Purposes For Process Managementmentioning
confidence: 99%
“…A new set of tools and standards has been developed in the last decade in order to define these business process models, grouped under the name of Business Process Management (BPM), facilitating enterprises to detail their business practices, understanding these as frequently repeated acts, habit or custom performed to a recognized level of skill (Lock Lee, 2005). BPM standards are able to deal with goals and tasks specification, environmental analysis, design, implementation, enactment, monitoring and evaluation of business processes (Muehlen & Ho, 2006).…”
Section: Introductionmentioning
confidence: 99%